Oral cancer in young adults: should we approach these patients differently? - Szewczyk, Mateusz; Pazdrowski, Jakub; Golusiński, Paweł; Więckowska, Barbara; Golusiński, Wojciech (Frontiers in Oncology, 2024)
The influence of age on treatment outcomes in oral cancer is unclear. We aimed to determine the prevalence of oral cancer in adults under age 45 and to compare treatment outcomes by age.Methods: Retrospective study of 284 patients treated for oral cancer from 2010 to 2021. The primary analysis involved the full cohort stratified by age (< vs. ≥ 45y). The second analysis included all patients under age 45 (n=44) matched 1:1 by sex and stage to older patients (age 55-70).In the primary analysis, the only significant difference was more comorbidities in the older group (p<0.001). In the matched-pair analysis, older patients were more likely to be smokers (75% vs. 54%; p=0.045) and had more comorbidities (p=0.007). The mean PLR and NLR values were significantly higher in the younger group.Conclusions: No significant differences were observed between age groups in disease stage or outcomes, suggesting that other variables are more important.